The wandering hill eaudiobook - McMurtry, Larry (Berrybender Narratives, 2017)
Author of more than 30 books and winner of the Pulitzer Prize, Larry McMurtry has gained international fame for his eccentric characters and vivid settings. The Wandering Hill is part of a series as colorful as the American West. An eccentric family of English sportsmen have traveled to America to hunt buffalo and other big game. As they spend the winter at a remote trading post, bizarre adventures and even stranger domestic affairs befall them.